MENGEMBANGKAN MOTORIK HALUS ANAK KEGIATAN MENIRU BENTUK MENGGUNAKAN PJBL, DEMONSTRASI DAN MEDIA KERTAS KOKORU - Andini, Mita; Novitawati, Novitawati (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
The problem in this study is the low fine motor skills of children in imitating shapes. This is because the learning presented tends to be monotonous, focused on writing, reading and counting activities, so that it ignores the development of children's fine motor skills in imitating shapes. Efforts to solve this problem are using the Project Based Learning model, Demonstration Method and Kokoru Paper Media. The purpose of this study is to describe teacher activities, analyze children's activities and analyze the improvement of children's fine motor skills. The approach to this research uses a qualitative approach with the type of Classroom Action Research (CAR) with 4 meetings. The subjects of this study were children in group B2 of TK Negeri 1 Alalak, totaling 17 children. Data analysis uses descriptive analysis using tables and graphs. Indicators of success are teacher activity reaching